Management of denture foreign body in esophagus with cervical esophagotomy: case report - Kadek Yudi Fajar Mahendra; Ketut Putu Yasa (DiscoverSys Inc., 2019)
Introduction: Impaction of dentures in the esophagus is a distressing experience for a patient and can lead to serious consequences, such as esophageal perforation. Patients with an impacted denture often present with a history of accidental swallowing, frequently during trauma, seizures, or sleep or in association with some degree of psychological dysfunction. The common signs and symptoms of an impacted denture are odynophagia, dysphagia, or simply pain and tenderness in the neck or chest.The preferred method of removal of esophageal foreign bodies is extraction with the flexible endoscope. Surgical removal is rarely indicated except in the event of perforation or other foreign body complications.In situations where this appears potentially hazardous, such as with impacted denture, open surgical extraction by cervical oesophagotomy is promptly performed is a safe option.Cases Report: The successful removal of impacted denture in the esophagus in a patient is reported, with a review of the literature. A women23-year-oldÂ complained of dysphagia after swallowing his denture. Following unsuccessful attempts at removal via a rigid esophagoscope, open surgery was performed. Without further delay, the impacted denture was removed by cervical oesophagotomy, and the patient recovered uneventfully.Conclusion: The successful removal of impacted denture by cervical oesophagotomy in the esophagus in a patient is reported. We conclude that cervical esophagotomy is a safe method for removing foreign bodies impacted in the cervical esophagus when they cannot be removed endoscopically.